Inovasi Manajerial dalam Membangun Jiwa Kewirausahaan: Studi Kasus Pesantren Muhammad Daud - Fikri Finandi Putra; Sukon Awaludin; Tsani Nur Sholehudin (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2026)
Global economic changes and industrial dynamics demand that Islamic education be oriented not only toward academic achievement but also toward strengthening character, life skills, and an entrepreneurial spirit. This study aims to analyze a values-based entrepreneurial management model in Islamic boarding schools (pesantren) and its contribution to institutional independence and the development of students' entrepreneurial spirit. The study employed a qualitative descriptive approach with participatory observation and documentation studies, analyzed interactively through data reduction, presentation, and verification. The results indicate that Islamic boarding school entrepreneurship is developed through integrated local asset management within the learning process, using a collaborative model between administrators, educators, students, and the community. The integration of production activities into the curriculum not only improves students' technical skills but also fosters values ​​of responsibility, cooperation, and social concern. Implementation challenges, such as limited resources and market dynamics, are addressed through managerial innovation and strengthening internal economic institutions. This model significantly contributes to the institution's financial independence and expands the social function of Islamic education. The findings of this study strengthen the theoretical framework of values-based social entrepreneurship in Islamic educational management, affirming that the integration of knowledge, charity, and economic production can be a sustainable strategy for empowering educational institutions and communities. This model offers practical and conceptual implications for the development of Islamic education that is adaptive, contextual, and oriented towards economic empowerment.